Opredelitev tujejezikovne sporazumevalne zmožnosti v Skupnem evropskem jezikovnem okviru - Skela, Janez (Sodobna pedagogika, 2011)
The article is principally about communicative competence as the ultimate goalof foreign language teaching and learning. With the help of a framework for the conceptualisation of the contents of language syllabuses, the article traces the main developmental stages that have resulted in how the construct of communicative competence is understood today. The article then moves on to examine the most comprehensive treatment of communicative competence so far, as proposed by the Common European Framework of Reference for Languages: Learning, Teaching, Assessment (CEFR or Framework). The article then deals with the "teaching" of communicative competence. It is established that today's mainstream foreign language teaching pedagogy (i.e. the communicative approach) has not yet developed systematic means for the teaching of communicative competence. Communication in a foreign language is, after all, something so complex that it will probably never be reduced to "a neatly packaged syllabus". Because of the special status of English, which has emerged as a world lingua franca, and because of the need for more effective ways of "teaching" communicative competence, the concept of "best practice" ischanging all the time. All over the English-speaking world, new hybrid models of ELT pedagogy are emerging, which, in their various guises, combine features of both EFL and ESL schools of thought and practice, thus bringing ESL into the ELT fold.
Keywords: jezikovni pouk; language teaching; metodika; foreign languages; communicative competence; tuji jeziki; sporazumevalna zmožnost; Common European Framework of Reference for Languages; CEFR; Skupni evropski jezikovni okvir; hybrid models of foreign langauge teaching; SEJO